2011
DOI: 10.1136/bmjqs-2011-000088
|View full text |Cite
|
Sign up to set email alerts
|

Understanding ethnic and other socio-demographic differences in patient experience of primary care: evidence from the English General Practice Patient Survey

Abstract: BackgroundEthnic minorities and some other patient groups consistently report lower scores on patient surveys, but the reasons for this are unclear. This study examined whether low scores of ethnic minority and other socio-demographic groups reflect their concentration in poorly performing primary care practices, and whether any remaining differences are consistent across practices.MethodsUsing data from the 2009 English General Practice Patient Survey (2 163 456 respondents from 8267 general practices) this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
221
2
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 147 publications
(250 citation statements)
references
References 20 publications
25
221
2
2
Order By: Relevance
“…Observed differences in reported respect by age, gender and ethnicity are consistent with past studies on cancer patients' experiences of respect [25] and overall care [28] and similar disparities in patient experience of healthcare professional communication by age, gender and/or ethnicity have been observed in the general UK patient population [29,30]. Past studies with US general patient samples have likewise shown younger and non-White patients to be less likely to report always being treated with respect and dignity but no difference by gender [12,13].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Observed differences in reported respect by age, gender and ethnicity are consistent with past studies on cancer patients' experiences of respect [25] and overall care [28] and similar disparities in patient experience of healthcare professional communication by age, gender and/or ethnicity have been observed in the general UK patient population [29,30]. Past studies with US general patient samples have likewise shown younger and non-White patients to be less likely to report always being treated with respect and dignity but no difference by gender [12,13].…”
Section: Discussionsupporting
confidence: 78%
“…However, this is unlikely to explain all differences in reported respect since differences in patient experience of care remain after adjusting for care site [29,33]. Differences in reported respect could be due to some patient groups being treated with less respect, possibly because of less respectful attitudes towards certain patients [24,35] and/or to differences in patient groups' conceptions and expectations of quality care [30].…”
Section: Discussionmentioning
confidence: 75%
“…All craving measures were taken immediately before the intervention and immediately after (16 studies) or 5 minutes after the intervention (3 studies). To facilitate the use of linear regression modelling and to assist with interpretation of the results, all responses on the 1-7 scale were linearly rescaled to a range of 0-100 (Lyratzopoulos et al 2012). Thus, a mean difference between groups of -10 would indicate that post-intervention cravings were 10 percentage points lower in the intervention group compared with the control group.…”
Section: Cravings Measuresmentioning
confidence: 99%
“…Changes in affect were suggested to mediate the acute effects of PA on cigarette cravings (Taylor et al 2007), hence we included measures of affect (FAS and FS) as potential mediators in our analyses. Similarly to the cravings outcomes, to facilitate interpretation of results and to calculate change scores for affect, both FS (measured on a Likert scale of -5 to +5) and FAS (measured on a Likert scale of 1-6) scores, were linearly rescaled to 0-100 (Lyratzopoulos et al 2012). …”
Section: Potential Predictors Moderators and Mediatorsmentioning
confidence: 99%
See 1 more Smart Citation